Applications of Advanced Ceramics in Science, Technology, and Medicine - Babu, K. Chandra (Frontiers in Ceramic Science Ser., 2020)
Applications of Advanced Ceramics in Science, Technology, and Medicine explores a broad range of advanced ceramic materials and their innovative applications in distinct fields. Chapters cover applications such as actuators, energy storage, environmental health and monitoring, 3D printing, electronics, biomedical engineering and EMI shielding. Chapters provide readers with an overview of the structural and fundamental properties, synthesis strategies and versatile applications of advanced ceramic materials and their composites. The information in the volume will be beneficial for students, res.